The event in the poetry of long and short songs in Kurdish folk literature - Azad Mohammed Saed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Songs are divided into different forms, according to the criteria used between one division: art, songs, folk songs and folk songs i.e. traditional epic dealing with events and things from our worldly world such as man, nature, love, adventure, friendship, war, nostalgia, aspirations, hatred, memories, and masculinity, in addition to its main theme death And a struggle for survival and its attachment to life, on the one hand the characters are the heroes of the epics, most of them are human beings around a human being who cares about his accomplishments and his exploits and his heroic, the epics are concerned with life and problems and passion and the riddle of death and life and the world after death and eternity and A witness to this sees the epic of Gilgamesh, and one of his most important personalities is Gilgamesh, Ankido and Ishtar. This epic was written four thousand years ago in cuneiform in the time of the Sumerian, Assyrian and Babylonian. The first section defines and the concept of poetry, songs, and epics, and in the branch, poetry deals with songs and epics in theory, and in the second topic in the first section, the difference between poetry, songs, and epics, in the second branch of the second topic, the research deals with samples of Kurdish poetry and lyrics. Zj of Kurdish epics, where he concludes with a summary and Balkhatmh in Arabic and English with a list of sources in Kurdish and Arabic.